Conventionalization, expectation, politeness and pragmatic impact: A German perspective - Stadler, Stefanie (Linguistik Online, 2025)
While politeness has originally been closely associated with indirectness in early politeness research, the field has since moved to a view that conventionalized indirectness tends to be the preferred option by interlocutors. The approach to conventionalization posits that conventionally indirect forms are considered to be the most polite. However, equating indirectness to politeness has been shown to be problematic. While indirectness may well remain an important construct within some cultural contexts, this certainly does not hold across all cultures and lingua-practices. This paper discusses the relevance of the concepts of conventionalization vs. expectation as a research construct and explores the link between communicative conventions, expectation, politeness and pragmatic impact within a German cultural framework. The data indicates that while many Anglo-Saxon cultures express face concerns and relational work through overt politeness markers and avoid direct communication, German culture does not show a dispreference for directness. The insights from this paper further reinforce this well-documented tendency. Furthermore, the findings suggest that relational work is actually achieved via the use of explicit, direct communication and modal particles that express contradiction. The evidence suggests that greater confrontational responses to the previous speaker can equal greater support of the conversational partner.